Development of Distributed Database Architecture for Financial Information Systems in Multinational Companies: A Case Study of PT. Syntax Corporation Indonesia - Solikhah, Mar'atus; Selamat, Rachmat; Tjahjadi, Djajasukma (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2025)
Multinational companies face challenges in managing financial data spread across various global branches. Distributed database architecture is considered a solution to integrate and manage data more efficiently and securely. PT. Syntax Corporation Indonesia as a multinational company has implemented this system, but its impact on the efficiency of financial data management and decision-making needs to be studied further. This research aims to explore the application of distributed database architecture in financial information systems in PT. Syntax Corporation Indonesia, as well as analyzing its impact on operational efficiency, risk management, and financial decision-making. This study uses a descriptive-qualitative approach with case studies. Data was collected through interviews with relevant stakeholders, questionnaires to system user staff, and documentation related to system implementation and evaluation. The data were then analyzed using thematic analysis techniques and descriptive statistics. The implementation of distributed database architecture at PT. Syntax Corporation Indonesia has succeeded in improving the efficiency of financial data processing, accelerating decision-making, and improving system reliability. However, challenges related to the cost of implementation and staff training remain a major obstacle. This research provides recommendations for strengthening IT infrastructure and ongoing training for company staff.